Guru PAI dalam Menerapkan Kurikulum Merdeka Pada Kelas Rendah di Madrasah Ibtidaiyah Al Ula - Bakri, Anisa (Darajat: Jurnal Pendidikan Agama Islam, 2024)
The Merdeka Curriculum, as an alternative curriculum, overcomes the pandemic's learning setbacks and grants teachers and school principals the "Freedom to Learn" freedom to plan, carry out, and develop curricula in schools while taking into account the needs and potential of their students. The purpose of this study is to ascertain how PAI teachers at the Madrasah Ibtidaiyah Al Ula school contribute to the Merdeka curriculum's implementation. The study was carried out utilizing a descriptive qualitative methodology. The Madrasah Ibtidaiyah Al Ula Classes 4-6 pupils serve as the sample or object of the investigation. Interviews and observation were the author's methods of data collection. The research's findings demonstrate that Madrasah Ibtidaiyah's implementation of the independent curriculum is proceeding smoothly because it conforms well to the requirements of Islamic religious education, which calls for its delivery in phases and a foundation in the most crucial subjects—Aqidah, the Qur'an, Hadith, Jurisprudence, Morals, and Date. Thus, the guidance and assistance needed to implement the Merdeka curriculum at MI Al Ula is the responsibility of the PAI teachers.